The research process in nursing - Gerrish, Kate, 1955-; Lacey, Anne; Cormack, Desmond (Blackwell Pub., 2010)
"The ability to understand, appraise and utilise research evidence is central to providing high quality healthcare. Research capacity building in the profession also means that nurses need to learn the skills to undertake research for themselves. The Research Process in Nursing serves as an introduction for novice nurse researchers to the process of undertaking empirical research, critically appraising published research and implementing research findings in practice. The sixth edition of this well established research text is designed for nurses undertaking educational courses in research from pre-registration to masters' level and beyond. It is also designed to help nurses in clinical practice who are involved in research, and those who need to understand and implement research findings in practice. The Research Process in Nursing meets the needs of those seeking to undertake research by providing a comprehensive account of the stages involved in the research process, including preparing research proposals, research designs, methods of data collection and analysis and writing research reports. Each chapter begins with a bulleted list of key points, and ends with a short conclusion, references, reading list, and relevant websites"--Provided by publisher.